Tingkat Stress Akademik Mahasiswa Prodi Statistika Angkatan 24 dan Coping Mechanismnya yang Efektif di Universitas Negeri Medan - Febi Hijriana; Femi Ezrani Siantur; Nur Maulidya Rizky; Raihan Riyadi Siregar; Putri Maulidina Fadilah; Sudianto Manullang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify the academic stress levels and coping mechanisms used by 2024 cohort students of the Statistics Study Program at Universitas Negeri Medan. A descriptive quantitative method was applied, involving questionnaires and interviews. Data were collected from 50 randomly selected respondents. The instrument was tested for validity and reliability, with all items showing item-total correlations > 0.2787 and a Cronbach’s Alpha score of 0.619, indicating acceptable reliability. The findings revealed high levels of academic stress, particularly in indicators such as feeling overwhelmed by deadlines (mean 3.82; 66%), exam anxiety (3.7; 66%), and lack of rest (3.6; 60%). The most dominant coping strategy was self-soothing (mean 4.44; 90%), followed by junk food consumption (3.5; 60%) and seeking help (3.42; 46%). In contrast, proactive strategies such as creating a to-do list were less commonly used (3.14; 38%). These results highlight the importance of adaptive coping training and psychological support to promote healthier stress management among students.